Clinical and economic analysis of patients with acute myeloid leukemia by FLT3 status and midostaurin use at a Comprehensive Cancer Center. (December 2019) - Willis, Connor; Menon, Jyothi; Unni, Sudhir; Au, Trang; Yoo, Minkyoung; Biskupiak, Joseph; Brixner, Diana; Ndife, Briana; Joseph, George; Bonifacio, Gaetano; Stein, Eytan; Tantravahi, Srinivas; et al.
Highlights: FLT3m patients had fewer cycles of consolidation and shorter time to transplant. Survival was similar between FLT3m and FLT wildtype. AML related inpatient charges were higher for FLT3m patients. Abstract: Introduction: Identification of cytogenetic and molecular abnormalities has become vital for the appropriate treatment of acute myeloid leukemia (AML). One of the most common molecular alterations in AML is the constitutive activation by internal tandem duplication of FMS-like tyrosine kinase 3 ( FLT3) . Methods: This observational, retrospective, cohort study at the Huntsman Cancer Institute (HCI) had two time periods: 1) a historical pre-midostaurin time period which consisted of the FLT3 mutated (FLT3m) and FLT3 wild type (FLT3wt) cohorts from January 1, 2007, to December 31, 2016, and 2) a post-midostaurin cohort which consisted of the FLT3 mutated midostaurin-user cohort (early mido) from May 01, 2017 to December 31, 2018. Results: In total, 39 patients were included in the FLT3m cohort, 61 in the FLT3wt cohort, and seven in the early mido cohort. FLT3m patients spent fewer days in the hospital during the first consolidation regimen and received fewer consolidation cycles compared to FLT3wt patients. Overall survival (OS) was similar between FLT3m and FLT3wt patients. For patients without hematopoietic stem cell transplant, OS was significantly shorter for FLT3m patients compared to FLT3wt patients. Mean AML related inpatient charges and physician charges for FLT3m patients were significantly higher than FLT3wt patients. Conclusion: The FLT3 mutation is historically associated with a shorter time to transplant and increased total health care charges. More information is needed to evaluate the real-world treatment strategies for FLT3-mutated patients in the presence of FLT3 inhibitors and the impact of these treatment strategies on clinical and economic outcomes.